The performance of a spark-ignition engine fuelled with natural gas and gasoline - Aslam, M.U.; Masjuki, Haji Hassan; Kalam, M.A.; Abdesselam, H.; Varman, M.; Mahlia, T.M.I.; Amalina, M.A. (2005)
An experimental evaluation has been made of the power output, specific fuel consumption and fuel conversion efficiency from running a 1.5 litre, 4-cylinder Proton Magma retrofitted spark ignition car engine with a dynamometer. Tests have been conducted at wide open throttle (WOT), with varying speeds and at constant speed with varying load. Performance, fuel consumption measurements were recorded under steady state operating conditions for gasoline and CNG (compressed natural gas). The engine was converted to computer integrated bi-fueling system from a gasoline engine and was operated separately either with gasoline or CNG using an electronically controlled solenoid actuated valve system. A PC based data acquisition and control system was used for controlling all the operation. A comparative analysis of the performance has been made for gasoline and CNG. With CNG operation on average, brake mean pressure and brake specific fuel consumption were found to decrease by around 16% and 18% respectively. However, in terms of fuel conversion efficiency, operation with CNG was found to be more efficient than with gasoline. This is due to the comparative lean operation of the engine with CNG compared to gasoline.